Parkinson’s Disease: Overview of Transcription Factor Regulation, Genetics, and Cellular and Animal Models - Xia, Ninuo; Cabin, Deborah E.; Fang, Fang; Reijo Pera, Renee A. (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD) is one of the most common neurodegenerative disorders, affecting nearly 7-10 million people worldwide. Over the last decade, there has been considerable progress in our understanding of the genetic basis of PD, in the development of stem cell-based and animal models of PD, and in management of some clinical features. However, there remains little ability to change the trajectory of PD and limited knowledge of the underlying etiology of PD. The role of genetics versus environment and the underlying physiology that determines the trajectory of the disease are still debated. Moreover, even though protein aggregates such as Lewy bodies and Lewy neurites may provide diagnostic value, their physiological role remains to be fully elucidated. Finally, limitations to the model systems for probing the genetics, etiology and biology of Parkinson’s disease have historically been a challenge. Here, we review highlights of the genetics of PD, advances in understanding molecular pathways and physiology, especially transcriptional factor (TF) regulators, and the development of model systems to probe etiology and potential therapeutic applications.